Spontaneous splenic rupture: a case report and literature review - Liu, Xinxing; Fu, Tingliang; Li, Donghua; Geng, Lei; Sun, Shuai (Frontiers in Surgery, 2026)
Spontaneous splenic rupture in children is a rare condition with limited documented cases in the medical literature. It can occur in both enlarged and normal-sized spleens. Clinical manifestations may include abdominal pain, splenomegaly, diminished or absent bowel sounds, Kehr's sign, Ballance's sign, and abdominal guarding. Imaging studies (computed tomography and ultrasound) serve as crucial diagnostic tools for splenic rupture. Splenectomy is no longer considered standard treatment due to the associated risk of overwhelming post-splenectomy infection (OPSI). Current therapeutic approaches prioritize hemostasis and spleen preservation. Prognosis depends on timely diagnosis and adequate management. Therefore, clinicians must maintain high vigilance for patients presenting with unexplained acute abdominal pain accompanied by hemodynamic instability. This article reports a pediatric case of spontaneous splenic rupture and reviews the literature to summarize the pathophysiology, clinical features, and management strategies for this condition.